2021
DOI: 10.1096/fj.202101426r
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction in pathological processes of chronic liver disease during aging

Abstract: Aging is associated with gradual changes in liver structure and physiological/pathological functions in hepatic cells including hepatocytes, cholangiocytes, Kupffer cells, hepatic stellate cells (HSCs), and liver sinusoidal endothelial cells (LSECs). LSECs are specialized hepatic endothelial cells that regulate liver homeostasis. These cells actively impact the hepatic microenvironment as they have fenestrations and a thin morphology to allow substance exchange between circulating blood and the liver tissue. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 105 publications
0
12
0
Order By: Relevance
“…[1] In addition, the decrease in NO production in elderly LSECs is associated with the activation of HSCs and profibrotic pathways. [88,89] Interestingly, liver endothelial senescence, dysfunction, and the profibrotic features in aged animals can be attenuated by simvastatin, as well as by the activation of the Sirtuin 1-associated pathway. [1][2][3] Indeed, simvastatin administration to aged rats with cirrhosis reduced portal hypertension, endotheliumdependent vasodilatory capacity, increased LSEC fenestrae, and decreased matrix deposition.…”
Section: Aging and Senescencementioning
confidence: 99%
“…[1] In addition, the decrease in NO production in elderly LSECs is associated with the activation of HSCs and profibrotic pathways. [88,89] Interestingly, liver endothelial senescence, dysfunction, and the profibrotic features in aged animals can be attenuated by simvastatin, as well as by the activation of the Sirtuin 1-associated pathway. [1][2][3] Indeed, simvastatin administration to aged rats with cirrhosis reduced portal hypertension, endotheliumdependent vasodilatory capacity, increased LSEC fenestrae, and decreased matrix deposition.…”
Section: Aging and Senescencementioning
confidence: 99%
“…Moreover, LSECs suffer from increased oxidative stress and ramp up their production of proinflammatory cytokines. Other effects of age-related LSEC changes may include hepatic hypoxia, activation of hepatic stellate cells (HSCs), and liver fibrosis [70]. The latter is due to the well-established role of activated HSCs that are transdifferentiated into profibrotic myofibroblasts producing ECM components [71]; in addition, there is evidence for an involvement of bone marrow-derived myofibroblasts in the development of liver fibrosis [72].…”
Section: Sinusoidal Endothelial Cells and Hepatic Stellate Cellsmentioning
confidence: 99%
“…This is reversed at a later stage via an autocrine mechanism, as well as increased VEGFR-2 to begin the angiogenic phase. 59 Animal models have demonstrated that, as the angiogenic phase progresses, hepatocytes secrete hypoxia-induced angiogenic factors such as VEGF and angiopoietins that bolster LSEC proliferation until the population reaches its peak at around 3 to 4 days post PHx. 42 60 Finally, LSECs play a key role during the termination phase of liver regeneration by secreting TGF-β, which stimulates HSCs, contributes to reconstruction of the extracellular matrix (ECM) scaffold, and terminates hepatocyte regeneration.…”
Section: Asig In Hepatic Health and Regenerationmentioning
confidence: 99%